PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DEVIDEN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Indriani, Ila; Sari, Lita Permata; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
In this study, the company's primary data was taken from financial reports that were registered on the Indonesia Stock Exchange. The descriptive and quantitative methods used in this panel research were a population of 45 companies over 4 years from 2019-2022 and the total sample in this research was 9 companies using purposive sampling techniques. Based on the hypothesis test using the Smart PLS 3.0 application that has been carried out, the results show that company size and managerial ownership have no significant effect on financial performance and the liquidity variable has a significant effect on financial performance. Liquidity does not have a significant effect on dividend policy. Company size and liquidity do not have a significant effect on dividend policy. Financial Performance has a significant influence on Dividend Policy through Dividend Policy. Financial Performance has a significant positive effect on Dividend Policy through Dividend Policy. Company Size has an insignificant effect on Divide nd Policy through Financial Performance. Company size has no significant effect on Dividend Policy through Financial Performance. Company size has no significant effect on Dividend Policy through Financial Performance.